IMPLEMENTATION OF THE BUY THE SERVICE (BTS) PROGRAM TO SUPPORT COMMUNITY MOBILIZATION IN THE CITY OF MAKASSAR - Muhammad Rafi Akbar; Haedar Akib; Novayanti Sopia Rukmana; Juwita Pratiwi Lukman (Universitas Negeri Makassar, 2026)
The Buy The Service (BTS) program is a government subsidy program that entered Makassar City in 2021 where its operation until now still has problems such as conflicts with pete-pete groups so that the BTS Teman Bus is not running optimally. The purpose of this research is to find out; 1) How is the implementation of BTS Teman Bus in Makassar City; 2) to find out what are the inhibiting factors in the implementation of the BTS Teman Bus program in Makassar City. The type of research used is descriptive research using a qualitative approach. Data collection techniques were carried out by observation, interview, and documentation. Data analysis uses data reduction, data presentation and conclusion drawing. The results showed that; 1) The implementation of the BTS Teman Bus Program in Makassar City has gone well, although there are still shortcomings in its implementation. This is because the operation of BTS Teman Bus has not yet reached all routes in Makassar city; 2) The inhibiting factors in the implementation of the BTS Teman Bus program are caused by several factors, such as the number of prohibited stops, the closure of corridors 3 and 4 due to the reduction of subsidiesfrom the center to cashless payments. In this study, it is hoped that there will be supporting policies that can follow the sustainability of the BTS Teman Bus subsidy, such as the availability of bus stops to the completion of the bus stop point.